Analisis Pengaruh Tumpangsari Terhadap Pendapatan Petani Di Desa Munduktemu Kabupaten Tabanan - Windasari, Ni Putu Evi; Sri Budhi, Made Kembar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 5, Mei 2013 (pp. 226-276), 2013)
Agricultural land is increasingly narrows as well as necessities of life that the higher cause the decline in agricultural production and result in a decrease in people's income, especially farmers. Thus for efficient land use of farmers use intercropping farming system in perkebnannya. Intercropping is planting two or more types of plants on a land area of. The purpose of this research is to know the influence of land area, the number of Labor (hours of work) and the price of commodities simultaneously as well as partial to the income of farmers in the village of Munduktemu, know the variables that influence the dominant as well as find out if there are differences in the income of farmers with or without using intercropping systems. This research was conducted in the village of Pupuan, district Munduktemu, Tabanan Regency using samples as much as 92 people. Data analysis techniques used in the analysis of the multiple linear and two different average (pair sample t test). The results of data analysis shows the land area, the number of Labor (hours of work) and the price of commodities simultaneously and partial effect on farmer income with a coefficient of determination (R2) 0,912. Land area is the most dominant variable effect on farmer income as well as income-there is a difference with or without the use of intercropping systems.
Keywords: income , land area , labor , commodity prices , intercropping